2018
DOI: 10.1021/jacs.8b11529
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Additives Enable Native Mass Spectrometry Measurement of Membrane Protein Oligomeric State within Intact Nanodiscs

Abstract: Membrane proteins play critical biochemical roles but remain challenging to study. Recently, native or nondenaturing mass spectrometry (MS) has made great strides in characterizing membrane protein interactions. However, conventional native MS relies on detergent micelles, which may disrupt natural interactions. Lipoprotein nanodiscs provide a platform to present membrane proteins for native MS within a lipid bilayer environment, but prior native MS of membrane proteins in nanodiscs has been limited by the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(154 citation statements)
references
References 77 publications
(178 reference statements)
2
143
0
1
Order By: Relevance
“…To overcome these drawbacks, several means to reduce membrane protein charge have been reported. These include instrument modification, solubilization with different detergents, and addition of small molecules (14,15,13,16). Instrument modification is the most effective, though it is prohibitive for many groups (14).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these drawbacks, several means to reduce membrane protein charge have been reported. These include instrument modification, solubilization with different detergents, and addition of small molecules (14,15,13,16). Instrument modification is the most effective, though it is prohibitive for many groups (14).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of NMR, intact nanodiscs were identified via a characteristic sharp peak at 0ppm (80)(81)(82). By ESI-MS, nanodiscs generate a broad 'hump-like' peak resulting from incomplete desolvation and polydispersity in the number of lipids contained in individual nanodiscs ( Figure 2c) (83)(84)(85). Together, these data unambiguously demonstrate successful generation and purification of MSP1D1 H5 nanodiscs.…”
Section: Chromatographymentioning
confidence: 72%
“…110,111 A first study explored nanodiscs, bicelles and amphipols for native MS and showed that indeed the native oligomeric states of several integral membrane proteins were preserved in nanodiscs and bicelles while they differed from those obtained from detergent micelles or amphipols. 112 In particular, nanodiscs were therefore examined in detail; the complex and heterogeneous mass spectra further induced improvements in spectral deconvolution, [113][114][115][116] sample preparation [117][118][119] and method optimisation. 119,120 These improvements allowed, for instance, monitoring the insertion and oligomer assembly in the lipid bilayer.…”
Section: Unravelling the Architecture Of Membrane Protein Assembliementioning
confidence: 99%